Voyage vers un "altro paese" : - Raul Caplan (Babel : Littératures Plurielles, 1999)
Los Fuegos de San Telmo (1964) by José Pedro Diaz (Montevideo) is the account of a journey in Italy; the writer, who is also the narrator, was there to visit the village of Marina di Camerota, the birthplace of his uncle, an Italian immigrant who had died a few years before in Montevideo. The narrator had been reared with the stories about the village told by Uncle Domingo (Domenico, in Italian), and they had aroused in him the wish to become a writer; therefore the journey became an opportunity for him to compare imaginary and to a large extent mythical geography with reality.The purpose of this study is to bring to light the role played by the words of Italian origin that are used in the text. There are not many of them, but they link the past to the present, and the author’s childhood memories to their literary re-creation. The starting point for this story is only two proper nouns (the uncle’ name, and that of the village) and two common nouns (the name of a shark: the « pescecane », and the name of some bandits: the « briganti »). These words create a fertile network of connotations and their evocative power goes much further than their mere meaning which, sometimes, may even become of quite secondary importance. Thus they open the doors of literature for the writer-narrator: the child has grown into a man, and the traveller becomes a writer.